2021
DOI: 10.1002/jbt.22762
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin ameliorates oxidative stress and mitochondrial damage induced by multiwall carbon nanotubes in rat kidney mitochondria

Abstract: The toxicity of carbon nanotubes (CNTs) toward the mitochondria of the kidney is not fully recognized and still needs further research. Apigenin (APG) is known as a flavonoid compound and natural antioxidant. The purpose of this study was to assess the ameliorative role of APG against multiwall CNT (MWCNT)-induced kidney toxicity in rats. The animals were administrated with APG (10 mg/kg) for 2 weeks and then were exposed to MWCNTs (5 mg/m 3 ) in pure and impure forms (10 and 100 nm) for 5 h/day and 5 days/wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
(83 reference statements)
0
17
0
Order By: Relevance
“…Fermentation is considered to be a possible strategy not only to increase AAs but also to release insoluble bound phenolic compounds and thus to improve the poor bioavailability of grain phenolics [41]. In the present study, many phenolic compounds such as β-carotenol [42], eugenol [43], apigenin [44], 6-gingerol [45], cinnamic acid [46] and vanillic acid [47] were detected in high concentrations in fermented brown rice, and all of these have been reported as strong antioxidants, as well as able to reduce stress-related behaviors. Principal component analysis (PCA) was applied for better interpretations, and to avoid multicollinearity (Figure 3B) (Table S3).…”
Section: Phenolic Compounds In Brown Rice Samplesmentioning
confidence: 75%
“…Fermentation is considered to be a possible strategy not only to increase AAs but also to release insoluble bound phenolic compounds and thus to improve the poor bioavailability of grain phenolics [41]. In the present study, many phenolic compounds such as β-carotenol [42], eugenol [43], apigenin [44], 6-gingerol [45], cinnamic acid [46] and vanillic acid [47] were detected in high concentrations in fermented brown rice, and all of these have been reported as strong antioxidants, as well as able to reduce stress-related behaviors. Principal component analysis (PCA) was applied for better interpretations, and to avoid multicollinearity (Figure 3B) (Table S3).…”
Section: Phenolic Compounds In Brown Rice Samplesmentioning
confidence: 75%
“…NiONPs have important medical applications; unfortunately, they showed a significant toxic profile mainly due to pro-oxidative action [129]. Moreover, Zamani and collaborators indicated, in rats, that apigenin was effective in exerting renal mitochondrial protection and antioxidant action following the exposure of carbon nanotubes, which induce mitochondrial dysfunction and oxidative stress and accumulate in several organs and tissues, including kidneys, with consequent organ damage [130].…”
Section: Renoprotection Of Apigenin Against Oxidative Stress-induced Injurymentioning
confidence: 99%
“…The large surface area of CNTs triggered free radical overproduction [ 51 ]. These free radicals dominate the endogenous antioxidant enzymes leading to the damage of protein, lipids, and DNA and, finally, apoptosis [ 11 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the actual mechanism of CNTs toxicity has not been fully elucidated yet. Some researchers attributed these toxic effects to CNTs’ ability to interfere with the function of cellular components, particularly mitochondria, through the induction of oxidative stress and inflammation [ 8 , 10 , 11 ]. In vitro and in vivo toxicological studies revealed that MWCNTs had the potential to induce the production of inflammatory cytokines [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation